Calcium levels and limestone particle size in the diet of commercial layers at the end of the first production cycle - Pelicia, K; Garcia, Edivaldo Antonio [UNESP]; Móri, C [UNESP]; Faitarone, ABG [UNESP]; Silva, AP [UNESP]; Molino, AB [UNESP]; Vercese, F [UNESP]; Berto, da [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2009)
This study evaluated the effect of dietary calcium levels and limestone particle size distribution on first-cycle layer performance and egg quality. A completely randomized experimental design in 4x3 factorial arrangement (four Ca levels - 3.0, 3.5, 4.0, 4.5%; and three limestone particle size distributions - 100% fine, 50% fine and 50% coarse, 30% fine and 70% coarse) was applied, totaling 12 treatments with six replicates of eight birds each. The treatments did not influence the most of evaluated performance and internal and external egg quality parameters. However, limestone particle size distribution quadratically affected with percentage of defective eggs, with the lowest percentage obtained with the distribution 61.75% fine limestone and 38.25% coarse limestone. Increasing dietary Ca levels significantly increased eggshell weight per surface area and the percentage of Ca excreted in the feces. It was concluded that the combination of the highest dietary Ca level (4.5%) with 50% replacement of fine-particle limestone by coarse limestone results in better eggshell and increases the number of marketable eggs.
Keywords: Egg production; limestone; marketable eggs; nutrition; poultry